China’s Role in International Conflict Mediation and Its Implications for International Relations - Yuliantoro, Nur Rachmat (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2025)
This study examines China’s evolving role as a mediator in international conflicts, particularly its involvement in the Saudi-Iranian dispute and the Russia-Ukraine war. It underscores China’s evolution from a historically reclusive nation to a significant global actor, accentuating its “peaceful rise” policy. In doing so, the study employs a conceptual framework to analyze the evolution of China’s foreign policy. It examines China’s strategic deployment of soft power through cultural diplomacy, economic influence, and mediation initiatives. The study’s findings indicate that China’s mediation has contested traditional Western hegemony in conflict resolution by presenting an alternative approach centered on sovereignty and non-interference. Challenges persist regarding perceptions of bias, particularly in conflict such as the Russia-Ukraine war, where neutrality is scrutinized. Ultimately, this study underscores China’s increasing role as a mediator, capable of shaping global diplomatic norms while navigating complex geopolitical contexts.